Dynamic analysis of banana fiber reinforced high-density polyethylene/poly (ε-caprolactone) composites - Misra R.K.; Kumar S.; Sandeep K.; Misra A. (My University, 2025)
Banana fiber reinforced HDPE/PCL (high-density polyethylene/poly (ε-caprolactone)) composites have been prepared in the laboratory for the evaluation of mechanical properties. The tensile strength and Young's modulus of the HDPE/PCL blend attains saturation at approximately 20% by weight of PCL addition. Therefore, the 80:20 blend of HDPE/PCL has been selected as the matrix material. It has also been observed that the ductility of the HDPE/PCL blend drops rapidly by addition of more than 15% by weight of PCL. Reinforcement of the banana fiber in an 80:20 HDPE/PCL blend matrix shows improvement in ductility, tensile strength and Young's modulus. In order to study the dynamic response of this banana fiber reinforced HDPE/PCL composite plate, a multiquadric radial basis function (MQRBF) is developed. MQRBF is applied for spatial discretization and a Newmark implicit scheme is used for temporal discretization. The discretization of the differential equations generates a greater number of algebraic equations than the unknown coefficients. To overcome this ill-conditioning, the multiple linear regression analysis, based on the least square error norm, is employed to obtain the coefficients. Simple supported and clamped boundary conditions are considered. Numerical results are compared with those obtained by other analytical methods.